Building social accountability to improve reproductive, maternal, newborn and child health in Nigeria - Rachel Sullivan Robinson; Tariah Adams (BMC, 2022)
Abstract Background Like many places in Nigeria, Niger, a predominantly rural and poor state in the north of the country, has high fertility, low contraceptive prevalence, and high maternal mortality. This paper presents a descriptive, contextualized case study of a social accountability campaign run by the nongovernmental organization White Ribbon Alliance Nigeria to strategically mobilize collective action to demand quality maternal health care and improve government responsiveness to those demands. We treat maternal health as a component of reproductive health, while recognizing it as a less contested area. Methods Data come from more than 40 interviews with relevant actors in Niger State in 2017 and 2018 during the initial phase of the campaign, and follow-up interviews with White Ribbon Alliance Nigeria staff in 2019 and 2021. Other data include White Ribbon Alliance Nigeria's monthly reports. We analyzed these data both deductively and inductively using qualitative techniques. Results During its first phase, the campaign used advocacy techniques to convince the previously reticent state government to engage with citizens, and worked to amplify citizen voice by hosting community dialogues and town halls, training a cadre of citizen journalists, and shoring up ward health development committees. Many of these efforts were unsustainable, however, so during the campaign's second phase, White Ribbon Alliance Nigeria worked to solidify state commitment to durable accountability structures intended to survive beyond the campaign's involvement. Key challenges have included a nontransparent state budget release process and the continued need for significant support from White Ribbon Alliance Nigeria. Conclusion These findings reveal the significant time and resource inputs associated with implementing a strategic social accountability campaign, important compromises around the terminology used to describe "accountability," and the constraints on government responsiveness posed by unrealistic budgeting procedures. The campaign's contributions towards increased social accountability for maternal health should, however, also benefit accountability for reproductive health, as informed and empowered woman are better prepared to demand health services in any sector.